THE CURRENT STATE OF ENTREPRENEURIAL COMPETENCE FORMATION OF BACHELORS IN THE ENTERPRISE ECONOMICS - І. Середіна (Київський національний університет імені Тараса Шевченка, 2020)
The article considers the current state of entrepreneurial competence formation of future bachelors in the Enterprise Economics in the professional training process. The analysis of the entrepreneurial competence content is presented in the context of the competence approach, with regard to entrepreneurship, as a leading form of management in market economy conditions. The current state of competence formation of future bachelors in the Enterprise Economics is defined as the process of the future bachelor's professional training in the Enterprise Economics, which is influenced by the general modern education content of our state. The article shows that the current state of entrepreneurial competence is a separate unit in the future bachelors' curricula, in which elements of academic and vocational education are gradually implemented, which are fixed in the process of practical training during the entire period of professional training in the Enterprise Economics.The analysis of scientific works has shown that economic thinking, training in marketing area, discipline, initiative, sense of responsibility, communicativeness, creative attitude to work occupy an important place in the future bachelors' entrepreneurial competence structure in the Enterprise Economics.According to the results of the research, future bachelors training in the Enterprise Economics at National Transport University, we have found out the current state of specialists entrepreneurial competence formation of this specialty. The future bachelors acquisition in the Enterprise Economics in the process of professional training the integral, general and professional competences is analyzed.

Актуальність дослідження зумовлена інтенсивним розвитком вищої економічної освіти в Україні та гострим запитом суспільства й вітчизняної економіки на підготовку фахівців, готових до реалізації професійної кар'єри в умовах розвитку малого бізнесу. У статті розглянуто сучасний стан формування підприємницької компетентності майбутніх бакалаврів з економіки підприємства у процесі фахової підготовки. Аналіз змісту підприємницької компетентності подано в контексті компетентнісного підходу, з огляду на підприємництво, як провідну форму господарювання в умовах ринкової економіки. Сучасний стан формування компетентності майбутніх бакалаврів з економіки підприємства визначено як процес професійної підготовки майбутнього бакалавра з економіки підприємства, на яку впливає зміст загальної сучасної освіти нашої держави. У статті доведено, що сучасний стан підприємницької компетентності входить відокремленою одиницею до навчальних планів майбутніх бакалаврів, в яких поетапно реалізуються елементи академічної та професійної освіти, що закріплюються у процесі практичної підготовки протягом усього терміну навчання фахівців з економіки підприємства.Аналіз наукових праць довів, що у структурі підприємницької компетентності майбутніх бакалаврів з економіки підприємства важливе місце посідають економічне мислення, підготовка у сферах маркетингу, дисциплінованість, ініціативність, почуття відповідальності, комунікативність, творче ставлення до праці.За результатами дослідження підготовки майбутніх бакалаврів з економіки підприємства в Національному транспортному університеті, нами з'ясовано сучасний стан формування підприємницької компетентності фахівців даної спеціалізації. Проаналізовано набуття майбутніми бакалаврами з економіки підприємства у процесі фахової підготовки інтегральних, загальних та професійних компетентностей.
СУЧАСНИЙ СТАН ФОРМУВАННЯ ПІДПРИЄМНИЦЬКОЇ КОМПЕТЕНТНОСТІ БАКАЛАВРІВ З ЕКОНОМІКИ ПІДПРИЄМСТВА
Keywords: майбутні бакалаври; підприємництво; економіка підприємства; підприємницька компетентність; ключова компетентність.; future bachelors; entrepreneurship; Enterprise Economics; entrepreneurial competence; key competence.